2003
DOI: 10.1046/j.1445-2197.2003.02728.x
|View full text |Cite
|
Sign up to set email alerts
|

Imprint cytology versus frozen section: intraoperative analysis of sentinel lymph nodes in breast cancer

Abstract: Intraoperative analysis of sentinel lymph nodes in breast cancer can be performed quickly. Imprint cytology and frozen section show comparable accuracy in predicting sentinel node status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…In five of these studies 7,20,34,44,45 not all of the patients had both techniques performed; they were excluded from analysis to avoid the introduction of bias. Independent assessment of the touch imprint and frozen section methods was performed by Nagashima et al 5 The same pathologist examined both the frozen section and the imprint in the study of Sauer et al 29 .…”
Section: Study Results and Quality Appraisalmentioning
confidence: 99%
See 3 more Smart Citations
“…In five of these studies 7,20,34,44,45 not all of the patients had both techniques performed; they were excluded from analysis to avoid the introduction of bias. Independent assessment of the touch imprint and frozen section methods was performed by Nagashima et al 5 The same pathologist examined both the frozen section and the imprint in the study of Sauer et al 29 .…”
Section: Study Results and Quality Appraisalmentioning
confidence: 99%
“…There were nine studies in which the sentinel lymph node was processed for frozen section examination after an imprint cytology slide had been prepared 5,7,12,20,29,33,34,44,45 . In five of these studies 7,20,34,44,45 not all of the patients had both techniques performed; they were excluded from analysis to avoid the introduction of bias.…”
Section: Study Results and Quality Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…This process can be achieved by means of frozen sectioning (FS) and touch imprint cytology (TIC). Results of numerous studies showed that TIC has a sensitivity equivalent to or even better than that of FS (2)(3)(4)(5), since TIC offers the advantages of minimal tissue preparation, rapid staining and good cytological detail for interpretation. No special equipment is required and no tissue loss occurs (6).…”
Section: Introductionmentioning
confidence: 99%